2020
DOI: 10.2478/foecol-2020-0015
|View full text |Cite
|
Sign up to set email alerts
|

Known and predicted impacts of the invasive oak lace bug (Corythucha arcuata) in European oak ecosystems – a review

Abstract: The North American oak lace bug (OLB, Corythucha arcuata) was first found in Europe in northern Italy in 2000, and up to 2019 it was recorded in 20 countries. Almost all Eurasian deciduous oak species are suitable hosts and the species can also feed on many other woody plants. At least 30 million hectares of oak forests provide suitable hosts for the OLB, meaning that the lack of suitable hosts will not restrict its further spread. Detailed studies on the long-term impact of the species are not yet available b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
54
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(56 citation statements)
references
References 29 publications
2
54
0
Order By: Relevance
“…While some of them do not have any evident impact in the newly colonized areas, others may become invasive, rapidly expanding their area and imposing severe pressure on the invaded area's ecosystems both from an economic and an ecological point of view. The chance of a non-native species becoming invasive strongly depends on the suitability of the environmental conditions including availability of host plants (Csóka et al 2019;Paulin et al 2020), effects of native natural enemies (Csóka et al 2009;Panzavolta et al 2018;Kos et al 2020). The weather and climate may also be decisive factors from the point of the establishment and the future of the established populations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…While some of them do not have any evident impact in the newly colonized areas, others may become invasive, rapidly expanding their area and imposing severe pressure on the invaded area's ecosystems both from an economic and an ecological point of view. The chance of a non-native species becoming invasive strongly depends on the suitability of the environmental conditions including availability of host plants (Csóka et al 2019;Paulin et al 2020), effects of native natural enemies (Csóka et al 2009;Panzavolta et al 2018;Kos et al 2020). The weather and climate may also be decisive factors from the point of the establishment and the future of the established populations.…”
Section: Introductionmentioning
confidence: 99%
“…The North American oak lace bug (Corythucha arcuata (Say 1832) -Heteroptera: Tingidae) is a recent invader in Europe, first discovered in Italy in 2000 (Bernardinelli et al 2000). In the last decade, it showed an explosive area expansion and has been reported from 20 European countries (Paulin et al 2020). As almost all native deciduous oaks are suitable hosts for the oak lace bug (OLB), at least 30 million hectares of oak for-ests provide acceptable hosts for it in Europe (Csóka et al 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the fruit and nut breeding Nearctic insect Chymomyza amoena was assigned to the lowest impact category Minor concern (MC), because no negative impact on native host species was observed despite its rapid spread since its arrival to Europe in 1975. However, the impact classification of alien insects may increase in time, if more research on other mechanisms is conducted like the competition with native species, which was recently discussed by Paulin et al (2020) for North American oak lace bug (Corythucha arcuata). The feeding by C. arcuata can lead to a shortage of food for specialized oak-associated species and can cause larger negative impacts than previously expected (Paulin et al 2020).…”
Section: Variablesmentioning
confidence: 99%
“…However, the impact classification of alien insects may increase in time, if more research on other mechanisms is conducted like the competition with native species, which was recently discussed by Paulin et al (2020) for North American oak lace bug (Corythucha arcuata). The feeding by C. arcuata can lead to a shortage of food for specialized oak-associated species and can cause larger negative impacts than previously expected (Paulin et al 2020). Further, some invasive alien insects with a high negative environmental impact, such as the emerald ash borer (Agrilus planipennis), were not included for the EICAT assessment in this study, as the species was not yet found or is expected to currently occur in the Biosphere Reserve.…”
Section: Variablesmentioning
confidence: 99%